The effect of therapeutic exercise interventions on physical and psychosocial outcomes in adults aged 80 years and older: a systematic review and meta-analysis - Nicolson, PJA; Duong, V; Williamson, E; Hopewell, S; Lamb, SE (Human Kinetics, 2021)
This systematic review aimed to evaluate the effects of therapeutic exercise on physical and psychosocial outcomes in community-dwelling adults aged 80 years or older. Databases were searched from inception to July 8, 2020. Randomized controlled trials (RCTs) were screened by two reviewers who extracted data and assessed study quality. Sixteen RCTs (1,660 participants) were included. Compared to nonexercise controls there was no evidence of an effect of exercise on performance based (standardized mean differences: 0.58, 95% confidence interval: [−0.19, 1.36]; I 2: 89%; six RCTs; 290 participants; very low-quality evidence) or self-reported physical function (standardized mean differences: 1.35, 95% confidence interval: [−0.78, 3.48]; I 2: 96%; three RCTs; 280 participants; very low-quality evidence) at short-medium term follow-up. Four RCTs reporting psychosocial outcomes could not be combined in meta-analysis and reported varying results. Exercise appeared to reduce the risk of mortality during follow-up (risk ratio: 0.47, 95% confidence interval: [0.32, 0.70]; I 2: 0.0%; six RCTs; 1,222 participants; low-quality evidence).